2018
DOI: 10.1186/s12888-018-1837-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with health service utilisation for common mental disorders: a systematic review

Abstract: BackgroundThere is a large treatment gap for common mental disorders (CMD), with wide variation by world region. This review identifies factors associated with formal health service utilisation for CMD in the general adult population, and compares evidence from high-income countries (HIC) with that from low-and-middle-income countries (LMIC).MethodsWe searched MEDLINE, PsycINFO, EMBASE and Scopus in May 2016. Eligibility criteria were: published in English, in peer-reviewed journals; using population-based sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
191
7
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 262 publications
(262 citation statements)
references
References 123 publications
28
191
7
11
Order By: Relevance
“…Intriguingly, the gender differences often reported in studies from high-income countries were not replicated in this setting, and we found the opposite association between marital status and treatment-seeking that which is typically reported elsewhere (6,7,64). This demonstrates the importance of local data in identifying vulnerable groups for service planning, and provides suggestive evidence that processes believed to inhibit treatment-seeking in other cultural contextssuch as masculine ideals of self-sufficiency (65, 66) -may not apply in the same way to Indian populations.…”
Section: Who Seeks Health Care For Depression Symptoms?contrasting
confidence: 87%
See 1 more Smart Citation
“…Intriguingly, the gender differences often reported in studies from high-income countries were not replicated in this setting, and we found the opposite association between marital status and treatment-seeking that which is typically reported elsewhere (6,7,64). This demonstrates the importance of local data in identifying vulnerable groups for service planning, and provides suggestive evidence that processes believed to inhibit treatment-seeking in other cultural contextssuch as masculine ideals of self-sufficiency (65, 66) -may not apply in the same way to Indian populations.…”
Section: Who Seeks Health Care For Depression Symptoms?contrasting
confidence: 87%
“…Thirdly, the evidence did not support an association between treatment-seeking and disability or perceived need for health care, which is at odds with international evidence (7). In light of the high rates of general health service use, this may be because people with depression consider themselves to have other health problems, and attribute their disability and associated need for health care to these non-depression symptoms.…”
Section: Who Seeks Health Care For Depression Symptoms?mentioning
confidence: 83%
“…The 60 local subjects, including 30 depressed patients and 30 normal subjects, were recruited in this study. The inclusion criteria for subjects described as follows: (1) Age was between 18-65 years old; (2) Body mass index (BMI) was between 18-28 Kg / m 2 ; (3) No history of treatment with antipsychotic medication; (4) Duration of symptoms was between 1 to 24 months; (5) No history of treatment with antidepressant medication; (6) Currently in the acute episode with the Hamilton Depression Rating Scale for Depression (HAMD) score ≥ 24; (7) Other mental disorders such as axis І, personality disorder and mental retardation were excluded; (8) Psychotropic drugs were never used; (9) Diagnosis of depression in Patients group was made by two psychiatrists according to the Mini-International Neuropsychiatric Interview (MINI) [18]; (10) In Controls group, a diagnosis of mental disorder was excluded by two psychiatrists according to the MINI, and HAMD-17 score was < 7; (11) Patients group was de ned as Follow-up group after receiving the drug treatment.…”
Section: Methods 21 Participantsmentioning
confidence: 99%
“…In addition, a series of exclusion criteria, based on the previous work, were employed in this study to exclude the factors affecting gut microbiota [19]. Those include: (1) No somatic diseases known to affect the gut microbiota such as in ammatory bowel disease, immune system diseases, diabetes, etc. ; (2) Without antibiotics, probiotics or microbiological products used in recent 3 months; (3) Without the history of medical examination or surgery through the gastrointestinal tract in recent 6 months; (4) Without obvious changes in dietary habits or the presence of obvious diarrhea, constipation and other symptoms in recent 1 month.…”
Section: Methods 21 Participantsmentioning
confidence: 99%
“…Attitudinal barriers, such as preferring to manage problems on one's own, are generally more likely to be endorsed than structural barriers (18,24,27,28). Another reason on the demand-side for not seeking professional care is a low perceived need (27)(28)(29)(30). As can be expected, people with less disabling symptoms are least likely to seek help, but more worrying is that also a considerable amount of people with a severe mental health disorder do not perceive any need for mental health care (27,28,30).…”
Section: Introductionmentioning
confidence: 99%